Alu RNA Structural Features Modulate Immune Cell Activation and A-to-I Editing of Alu RNAs Is Diminished in Human Inflammatory Bowel Disease - Aune, Thomas M.; Tossberg, John T.; Heinrich, Rachel M.; Porter, Krislyn P.; Crooke, Philip S. (Frontiers in Immunology, 2022)
Alu retrotransposons belong to the class of short interspersed nuclear elements (SINEs). Alu RNA is abundant in cells and its repetitive structure forms double-stranded RNAs (dsRNA) that activate dsRNA sensors and trigger innate immune responses with significant pathological consequences. Mechanisms to prevent innate immune activation include deamination of adenosines to inosines in dsRNAs, referred to as A-to-I editing, degradation of Alu RNAs by endoribonucleases, and sequestration of Alu RNAs by RNA binding proteins. We have previously demonstrated that find that widespread loss of Alu RNA A-to-I editing is associated with diverse human diseases including viral (COVID-19, influenza) and autoimmune diseases (multiple sclerosis). Here we demonstrate loss of A-to-I editing in leukocytes is also associated with inflammatory bowel diseases. Our structure-function analysis demonstrates that ability to activate innate immune responses resides in the left arm of Alu RNA, requires a 5’-PPP, RIG-I is the major Alu dsRNA sensor, and A-to-I editing disrupts both structure and function. Further, edited Alu RNAs inhibit activity of unedited Alu RNAs. Altering Alu RNA nucleotide sequence can increases biological activity. Two classes of Alu RNAs exist, one class stimulates both IRF and NF-kB transcriptional activity and a second class only stimulates IRF transcriptional activity. Thus, Alu RNAs play important roles in human disease but may also have therapeutic potential.